(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article illustrates some issues of teaching in the Credit module system and its advantages and disadvantages in teaching students at Universities in the Uzbekistan. Moreover, the article shows some methods of developing speaking skills